Application of public key infrastructure in telecom operators - Congli WANG; Jinhua WANG; Weijia XUE (Dianxin kexue)
With the implementation of cryptography law,the application of cryptography in information system in China has been promoted to the legal level,which requires the application of public key infrastructure in the mutual trust of network entities to be strengthened.A scheme of constructing unified telecom public key infrastructure with strict hierarchical structure was proposed,that is,establishing a national telecom root CA as a trust anchor,and each major telecom operator becomes an independent sub-ca,forming a certificate trust chain of “national telecom root CA- telecom operator sub-ca” and providing PKI security services.This scheme can not only realize the mutual recognition between telecom operators,but also help unify the telecom public key infrastructure to become a globally trusted electronic authentication service provider,so as to have more influence and say in the formulation of international certification standards.